Economic and Social Implications of the Youth Unemployment in the Republic of Macedonia - Mojsovska, Silvana; Janeska, Verica (Ревија за социјална политика/Journal of Social Policy, 2014)
This paper deals with the youth unemployment in the Republic of Macedonia, as one of the chronic problems of the society. The paper aims to provide in-depth insight into the youth unemployment in the country from the perspective of the available labor market data, as well as discuss major economic and social implications and its impact on the human capital in the Republic of Macedonia. The analysis of the implications has been based on the state of affairs with regards to youth inactivity, youth unemployment rates and long-term youth unemployment, which are rather high and represent serious threat to the human capital in the country. Particular attention has been paid to the education and its impact on the structure and skillfulness of the youth, analyzed with regards to the labour market needs and limited possibilities for the young population to find stable and satisfactory job. Furthermore, the paper deals with poverty as one of the most severe implications from the long-term unemployment in the Republic of Macedonia, which implies intense processes of emigration and brain drain, in particular of the youth. The main findings of the paper are truly alarming as the youth unemployment causes rapid deterioration of human capital, through physical migration and a decrease of the skillfulness and competitiveness of the labor force due to long-term unemployment. This calls for prompt attention of the policy-makers for alleviation of the problem and prevention of long-term damage for the country.